Rites of mine - Warnock, Cindy, author; Voss, Gary Wayne, advisor; Williams, Ronald G., committee member; Lundberg, Thomas R., committee member; Ruby, Christine, committee member (Colorado State University. Libraries, 1993)
To view the abstract, please see the full text of the document.
Keywords: Symbolism in art